A Review of Chitosan in Oral Drug Delivery Formulations - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2024)
In recent decades, the utility of nanoformulations as medication delivery systems has grown. It is not always the best option due to gastrointestinal distress, restricted inadequate absorption, and solubility. The impact of the early hepatic transit is one of the biggest obstacles that drugs must get past to have a therapeutic effect. These materials have attracted a lot of attention because studies have shown that oral delivery can be significantly enhanced by controlled-release systems that use nanoparticles (NPs) made of naturally derived biodegradable polymers. Chitosan (CS) has several applications and qualities in the pharmaceutical and medical industries. The traditional medication delivery method has been completely transformed by NPs’ capacity to modify molecules and their structures. In the current environment, CS because of their small size, NPs are a valuable tool for novel drug delivery systems. The process of ionotropic gelation is not the only one used in this field; alternative techniques include solvent evaporation, polyelectrolyte complex, emulsification solvent diffusion, emulsification cross-linking, and microemulsion. Numerous drug delivery applications, such as CS NPs have been found to be beneficial for a range of utilization, encompassing mucosal and controlled administration of drugs, tissue engineering, delivery of non-viral genes, vaccines, ocular drugs, electrodeposition, delivery of drugs that target the brain, enhancement of stability, and efficient delivery of insulin.